Pluviosidade e movimentos de massa nas áreas de risco do Maciço de Jaburuna, Vila Velha–ES: um estudo de correlação como subsídio para boas práticas de proteção e defesa civil - Felix, Fernando de Almeida (2024)
The town of Vila Velha, placed on the Metropolitan Region of Grande Vitória, Espírito Santo, has been historically affected by mass movement, associated to extreme events of rain. The occurrence of those phenomenon in urban environments shows great potential to cause disasters and human, material, and environmental losses. This research has the objective of elaborating a study to estimate a correlation between rainfall and mass movements events, by means of an empirical based model of measured rain database and geodynamic process registers in the risk areas of Maciço de Jaburuna, Vila Velha – ES through the analysis of inspection report from municipality Civil Defense, in order to produce a subsidy to deploy early warning systems and to implement others good practices on Civil’s Protection and Defense. There were identified 43 geological occurrences registered in this location during the period of 2005 to 2022, surveying the specification of the landslide, the event date, the horary, the kind of rupture occurred and the geographic coordinates of each one of these processes, which could be correlated with the information obtained from the rainfall database built to this region. The evaluation of the correlation curves indicates the time intervals of 6 hours, 24 hours and 96 hours are the most influential in triggering landslides. Notably, the great intensity and short-term rains play a significant role. The analysis suggests that these rains can cause mass movement independently of early accumulated rainfall. The minimum values observed for geological events are 22.99 mm/6h, 39.22 mm/24h and 53.63 mm/96h, defined as monitoring thresholds at the observation level. Values above 39.22 mm/6h, 39.22 mm/24h and 58.08 mm/96h have been defined as attention level thresholds. As warning level thresholds, values above 93.91 mm/6h, 111.23 mm/24h and 132.05 mm/96h were established.